ADAR2 Is Involved in Self and Nonself Recognition of Borna Disease Virus Genomic RNA in the Nucleus - Yanai, Mako; Kojima, Shohei; Sakai, Madoka; Komorizono, Ryo; Tomonaga, Keizo; Makino, Akiko (Journal of virology, 2020)
Cells sense pathogen-derived double-stranded RNA (dsRNA) as nonself. To avoid autoimmune activation by self dsRNA, cells utilize A-to-I editing by adenosine deaminase acting on RNA 1 (ADAR1) to disrupt dsRNA structures. Considering that viruses have evolved to exploit host machinery, A-to-I editing could benefit innate immune evasion by viruses. Borna disease virus (BoDV), a nuclear-replicating RNA virus, may require escape from nonself RNA-sensing and immune responses to establish persistent infection in the nucleus; however, the strategy by which BoDV evades nonself recognition is unclear. Here, we evaluated the involvement of ADARs in BoDV infection. The infection efficiency of BoDV was markedly decreased in both ADAR1 and ADAR2 knockdown cells at the early phase of infection. Microarray analysis using ADAR2 knockdown cells revealed that ADAR2 reduces immune responses even in the absence of infection. Knockdown of ADAR2 but not ADAR1 significantly reduced the spread and titer of BoDV in infected cells. Furthermore, ADAR2 knockout decreased the infection efficiency of BoDV, and overexpression of ADAR2 rescued the reduced infectivity in ADAR2 knockdown cells. However, the growth of influenza A virus, which causes acute infection in the nucleus, was not affected by ADAR2 knockdown. Moreover, ADAR2 bound to BoDV genomic RNA and induced A-to-G mutations in the genomes of persistently infected cells. We finally demonstrated that BoDV produced in ADAR2 knockdown cells induces stronger innate immune responses than those produced in wild-type cells. Taken together, our results suggest that BoDV utilizes ADAR2 to edit its genome to appear as "self" RNA in order to maintain persistent infection in the nucleus. Cells use the editing activity of adenosine deaminase acting on RNA proteins (ADARs) to prevent autoimmune responses induced by self dsRNA, but viruses can exploit this process to their advantage. Borna disease virus (BoDV), a nuclear-replicating RNA virus, must escape nonself RNA sensing by the host to establish persistent infection in the nucleus. We evaluated whether BoDV utilizes ADARs to prevent innate immune induction. ADAR2 plays a key role throughout the BoDV life cycle. ADAR2 knockdown reduced A-to-I editing of BoDV genomic RNA, leading to the induction of a strong innate immune response. These data suggest that BoDV exploits ADAR2 to edit nonself genomic RNA to appear as self RNA for innate immune evasion and establishment of persistent infection.